Evaluation of prescribing pattern and rationality of fixed dose combinations in patients of general medicine department - Joshi, Nupuri; Falke, Anvita; Saji, Sajin; Diwan, Arundhati; Raut, Asawari (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Fixed dose combinations are widely used in India, they are either irrational or prescribed irrationally. Moreover, the government has recently banned over 300 fixed dose combinations (FDCs) because of a lack of therapeutic justification. This study was conducted to study the prescribing pattern of FDCs in a tertiary care teaching hospital and to highlight the rationality of FDCs, and adverse drug reactions (ADRs) associated with them. Methods: In the present prospective observational study, a total of 500 inpatients were evaluated for prescribing pattern, cost analysis, and adverse drug reactions (ADRs) of FDCs. The FDCs were assessed for their rationality. The ADRs and severity were assessed using the WHO causality scale, Hartwig severity scale respectively. Results: Out of total 103 FDCs, 58 were approved, 86 were rational and 17 were irrational. 5 FDCs were banned and irrational. 48.54% of rational FDCs had rationality score from 7 to 9. The most commonly prescribed FDCs belonged to the anatomic therapeutic and chemical class of respiratory system, followed by anti-infectives in younger age group and cardiovascular FDCs in the elderly. The 886 ADRs occurred in 500 patients with a mean of 1.81±1.9. Banned FDCs contributed to 76 ADRs. According to causality and severity assessment, most of the ADRs were possible (62.53%) and mild (70.77%) respectively. Conclusions: Although FDCs were rational in most cases but banned FDCs were also prescribed. As these FDCs were associated with ADRs, monitoring of patients is necessary. Knowledge and attitude of healthcare professionals can be assessed through awareness programs.